The use of RAPD markers in the genetic analysis of the plant pathogenic fungus Cladosporium fulvum - Arnau, J.; Oliver, Richard (1994)
RAPD markers have been obtained in Cladosporium fulvum, in order to establish a genetic map based on mitotic recombination in this imperfect fungus. Segregation analysis has provided molecular evidence of a high degree of recombination during the parasexual cycle, and of the ploidy level of the parasexual progeny. A molecular study of 49 RAPDs obtained showed that, with only one exception, all RAPD markers studied represent repetitive DNA. This situation precludes the direct use of these markers to either initiate chromosome walking to a gene of interest or for the assignment of linkage groups to electrophoretically-separated chromosomes. A simple reamplification test has been applied which permitted the quick discrimination between single-copy and repetitive DNA species, without the need for Southern analysis. Additionally, evidence is shown for the presence of single-stranded DNA species in the amplification products, and that these may be present in addition to their double-stranded counterparts. The reamplification test can also identify these DNA species, avoiding misinterpretation of polymorphic bands.